2021
DOI: 10.1002/fsn3.2114
|View full text |Cite
|
Sign up to set email alerts
|

Smart edible films based on mucilage of lallemantia iberica seed incorporated with curcumin for freshness monitoring

Abstract: The objective of the present work was first to develop a smart packaging system based on Lallemantia iberica seed gum (LISG)/curcumin and, subsequently, investigate its physicochemical characteristics and biological activity. Finally, the response of LISG/curcumin films against pH change and the spoilage of shrimp were tested. The barrier properties and mechanical performance of the films improved as the curcumin concentration increased. FT‐IR analysis revealed the formation of physical interaction between LIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Kuswandi et al [ 139 ] used red cabbage anthocyanins immobilized on a bacterial cellulose membrane to develop a pH sensor that could be integrated into smart packaging and used to track the expiration dates of food products. Similarly, Taghinia et al [ 140 ] developed and detailed a smart packaging system for monitoring shrimp freshness using Lallemantia iberica seed gum and curcumin.…”
Section: Current Food Packaging Trendsmentioning
confidence: 99%
“…Kuswandi et al [ 139 ] used red cabbage anthocyanins immobilized on a bacterial cellulose membrane to develop a pH sensor that could be integrated into smart packaging and used to track the expiration dates of food products. Similarly, Taghinia et al [ 140 ] developed and detailed a smart packaging system for monitoring shrimp freshness using Lallemantia iberica seed gum and curcumin.…”
Section: Current Food Packaging Trendsmentioning
confidence: 99%
“…Rostami and Esfahani [ 95 ] reported that nanocomposite films based on Melissa officinalis seed gum films incorporated with montmorillonite and curcumin showed antimicrobial activity against Escherichia coli , Bacillus cereus , and Bacillus subtilis . Taghinia et al [ 96 ] observed that edible films based on Lalle-mantia iberica seed mucilage incorporated with curcumin showed antimicrobial activity against Escherichia coli , Bacillus cereus , Bacillus subtilis , and Penicillium expansum . Similarly, Manna et al [ 97 ] demonstrated that curcumin-loaded carboxymethylated guar gum can effectively inhibit the growth of gram-positive and gram-negative bacteria.…”
Section: Functional-edible-films Containing Curcuminmentioning
confidence: 99%
“…Curcumin and Lallemantia iberica seed gum, as the matrix, were used to develop films to monitor shrimp freshness [79]. Films were prepared by the casting method using tween 80 as emulsifier.…”
Section: Curcumin Used As Bio-based Sensormentioning
confidence: 99%